IDENTIFIKASI TUMBUHAN EPIFIT PADA TANAMAN KELAPA SAWIT DI DESA KAKULLASAN KECAMATAN TOMMO KABUPATEN MAMUJU SULAWESI BARAT - Trisferni; wulan, suci; Hasyim, Ahmad (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine the types of epiphytic plants found in oil palm plantations in Kakullasan Village, Tommo District, Mamuju Regency, West Sulawesi. Sampling was conducted using the exploration method, namely exploring the predetermined location using 4 plots measuring 10x10 m, then taking samples found and recording the condition of the location or place where the epiphytic plants grow. From the results of the study, ferns (Pteridophyta) were found and no moss (Bryophyta) was found. The total number of ferns from each plot was 88 consisting of 9 types of species divided into 5 classes of ferns, namely Pteridopsida, Filicopsida, Polypodiopsida, Filicinae and Gleicheniopsida. For the Pteridopsida class, 3 types of species were found, namely Drynaria quercifolia, Phymatosorus scolopendria and Nephrolepis exalata. The Filicopsida class found the species Dryopteris filix-mas and the Polypodiopsida class found the species Vittaria lineata. Filicinae class found 3 types of species, namely Asplenium nidus, Davalia solida and Davalia denticulate. Gleicheniopsida class found 1 type of species, namely Gleichenia linearis. The dominance index ranges between 0.002 - 0.023 which means that no species dominates because none of them are close to the value of 1, while the species diversity index is classified as high because the diversity index value is H’ = 1.206 or greater than 1 (H>1)